Small Intestinal Tuft Cell Activity Associates With Energy Metabolism in Diet-Induced Obesity - Arora, Pankaj; Andersen, Daniel; Moll, Janne Marie; Danneskiold-Samsøe, Niels Banhos; Xu, Liqin; Zhou, Biaofeng; Kladis, Georgios; Rausch, Philipp; Workman, Christopher T.; Kristiansen, Karsten; Brix, Susanne (Frontiers in Immunology, 2021)
Little is known about involvement of type 2 immune response-promoting intestinal tuft cells in metabolic regulation. We here examined the temporal changes in intestinal tuft cell number and activity in response to diet-induced obesity via intake of a high fat diet in C57BL/6J mice and investigated the relation to whole-body energy metabolism and the immune phenotype of the small intestine and epididymal white adipose tissue. Intake of high fat diet resulted in reduction in overall numbers of small intestinal epithelial and tuft cells and reduced expression of the intestinal type 2 tuft cell markers Il25 and Tslp. Amongst >1,700 diet-regulated transcripts in tuft cells, we observed an early association between body mass expansion and increased expression of the gene encoding the serine protease inhibitor neuroserpin. By contrast, tuft cell expression of genes encoding GABA-receptors was coupled to reduced body mass gain. Combined, we identify a role for small intestinal tuft cells in energy metabolism via regulation of distinct type 2 immune markers and gut-brain axis mediators. These results pave the way for further studies into interventions that elicit anti-obesogenic circuits via intestinal tuft cells.